Challenges And Reconstruction Of Regulations On The Responsibility Of Digital Platforms For The Misuse Of Personal Data In The Artificial Intelligence Ecosystem: A Contemporary Cyber Law Perspective - Gatot Sihombing, Indra; Krisnamurti, Hana; Pranadita, Nugaraha; Azhari, Arie; Setia Gunawan, Dini Eka; Permata Bunga, Dinda; Farida, Ade (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study examines cyber law issues in regulating the responsibility of digital platforms for the misuse of personal data based on Artificial Intelligence. The focus of the study is on the inconsistency between the development of autonomous technology and a legal framework that is still based on a conventional paradigm. This study uses a normative legal method with a legislative and conceptual approach to analyse the regulation of personal data protection and the legal responsibility of digital platforms. The results of the study show that existing regulations do not provide adequate legal certainty, particularly in terms of algorithm control and the division of legal responsibility. Therefore, it is necessary to reconstruct cyber law regulations that place digital platforms as active legal subjects with risk-based obligations and prevention principles. This reconstruction is expected to strengthen the protection of data subjects' rights and ensure the responsible use of Artificial Intelligence.